2006
DOI: 10.1164/rccm.200506-1006oc
|View full text |Cite
|
Sign up to set email alerts
|

Atelectasis Causes Alveolar Injury in Nonatelectatic Lung Regions

Abstract: These data support the notion that lung injury associated with atelectasis involves trauma to the distal airways. We provide topographic and biochemical evidence that such distal airway injury is not localized solely to atelectatic areas, but is instead generalized in both atelectatic and nonatelectatic lung regions. In contrast, alveolar injury associated with atelectasis does not occur in those areas that are atelectatic but occurs instead in remote nonatelectatic alveoli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
3
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(148 citation statements)
references
References 39 publications
7
131
3
7
Order By: Relevance
“…All lambs survived to the 3 h study. Pao 2 There were no differences between the LPS and salineexposed CMV groups for Paco 2 , V T , or oxygenation index. The CPAP group exposed to LPS had higher Paco 2 values than the saline-exposed lambs on CPAP, but V T and oxygenation index were similar over the 3 h study.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…All lambs survived to the 3 h study. Pao 2 There were no differences between the LPS and salineexposed CMV groups for Paco 2 , V T , or oxygenation index. The CPAP group exposed to LPS had higher Paco 2 values than the saline-exposed lambs on CPAP, but V T and oxygenation index were similar over the 3 h study.…”
Section: Resultsmentioning
confidence: 74%
“…M echanical ventilation of lungs from volumes below the normal functional residual capacity (FRC) cause injury by repetitively opening collapsed lung units (1,2). Similarly, ventilation with lung volumes that approach or exceed total lung capacity will stretch the lungs and cause injury (3,4).…”
mentioning
confidence: 99%
“…Kavanagh showed in a rat model of ARDS/ventilator‐induced lung injury that the major alveolar inflammatory response was localised not in atelectatic regions but in non‐dependent aerated regions. Distal airway injury occurred in both dependent and non‐dependent regions alike 14. Similarly, Terragni et al showed in human patients imaged with CT, that those in whom tidal ventilation was predominantly distributed to hyperaerated lung regions (and who also had larger areas of atelectasis) showed a greater inflammatory response – as measured by pulmonary cytokine concentrations – than those in whom tidal ventilation was predominantly distributed to normally aerated lung (and who also had smaller areas of atelectasis) 15.…”
Section: Dynamic Blood Gas Analysismentioning
confidence: 95%
“…Sections of 5 m were then stained with hematoxilin and eosin for light microscopic evaluation and scoring. A semi-quantitative analysis of inflammatory cell infiltration was assessed as previously described (20,21) using the following three parameters. Airspace Score: the presence of inflammatory cells in interalveolar septa; and the presence of inflammatory cells within alveoli; and Airway Score: peribronchiolar infiltration of inflammatory cells.…”
Section: B Ronchopulmonary Dysplasia (Bpd) Remains a Majormentioning
confidence: 99%